Acquired Duodenal Obstruction in Children - Jen-Hung Chien; Tsyr-Yuh Ho; Lin Shih-Peng; Chi-Ling Lee; Shan-Fu Ou (Pediatrics and Neonatology)
Traumatic intramural hematoma of the duodenum is a rare cause of acquired duodenal obstruction in children, and a high degree of suspicion is therefore required to make an early and accurate diagnosis. We report a 6-year-old boy whose epigastrium was impacted by the handlebar of his bicycle during a traffic accident. The boy then experienced epigastralgia. Six days later, progressive bilious vomiting suggestive of gastrointestinal obstruction was noted. Imaging studies revealed a large hematoma extending from the fourth portion of the duodenum to the jejunum. Conservative methods of treatment failed to manage his condition. He underwent laparoscopic surgery to evacuate the hematoma. We also report a case of duodenal obstruction in a previously healthy 2-year-old girl who presented for the first time with acute symptoms of proximal intestinal obstruction. Contrast examinations showed apparent barium retention over the stomach and proximal duodenum. She underwent surgery due to persistent obstruction, and a mushroom-like foreign body was detected embedded in the orifice of the windsock duodenal web. After duodenoduodenostomy and removal of the bezoar, she had a smooth recovery and tolerated feeding well. We conclude that blunt abdominal trauma and incomplete duodenal obstruction, such as that caused by duodenal web, should be considered as possible causes of acquired proximal gastrointestinal obstruction in previously healthy children, despite their rarity.